PENGARUH TINGKAT KETEPATAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN MEMBAYAR PBB-P2 DI DAWUAN - Janah, Siti Nurjanah (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2023)
This research is conducted to determine the influence of inaccuracy and taxpayer awareness on compliance in paying Land and Building Tax for Rural and Urban Areas (PBB-P2). This research falls under quantitative study, with a total of 100 respondents. The analysis tests employed are Validity Test, Reliability Test, Classic Assumption Test, and Multiple Linear Regression Equation Test using SPSS 25 application. Based on the research findings, it can be concluded that inaccuracy and taxpayer awareness have a positive and significant impact on taxpayer compliance in paying PBB-P2. The results of the T-test indicate that for variable X1, the significance is 0.000 < 0.05 and the t-score is 3.822 > t-table 1.661. Meanwhile, for variable X2, the significance is 0.000 < 0.05 and the t-score is 7.015 > t-table 1.661. Thus, there is a quality in the inaccuracy and taxpayer awareness that can affect taxpayer compliance in paying PBB-P2.